2021
DOI: 10.1016/j.celrep.2021.108953
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale 3D EM reconstructions reveal intrinsic mechanisms of structural diversity of chemical synapses

Abstract: Nanoscale 3D EM reconstructions reveal intrinsic mechanisms of structural diversity of chemical synapsesGraphical abstract Highlights d Chemical synapses have heterogeneous sizes, shapes, and organelle contents d This structural diversity is generated by mechanisms that are largely intrinsic d Structurally diverse synapses are organized in local connectomes stochastically d The morphological variability of specific synapse pools decreases with experience

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 96 publications
1
5
2
Order By: Relevance
“…The appearance of SP clusters likely reflects the elaboration and the stabilization of the spine apparatus (Perez‐Alvarez et al , 2020 ), that is, together with the presence of polyribosomes, predictive of activity‐dependent spine enlargement (Chirillo et al , 2019 ). In agreement with our results, a recent electron microscopy study performed in the intact hippocampus revealed that mushroom spines but not smaller protrusions (e.g., thin, stubby, or filopodial) exhibit higher volume and PSD size when contacted by TetTx + presynaptic terminals and more likely contained a spine apparatus (Zhu et al , 2021 ). The input‐specificity of SP recruitment upon activity perturbation is also supported by previous reports showing that high‐frequency stimulation in the dentate gyrus enhances SP immunoreactivity selectively in the corresponding stimulated layers (Yamazaki et al , 2008 ; de Solis et al , 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…The appearance of SP clusters likely reflects the elaboration and the stabilization of the spine apparatus (Perez‐Alvarez et al , 2020 ), that is, together with the presence of polyribosomes, predictive of activity‐dependent spine enlargement (Chirillo et al , 2019 ). In agreement with our results, a recent electron microscopy study performed in the intact hippocampus revealed that mushroom spines but not smaller protrusions (e.g., thin, stubby, or filopodial) exhibit higher volume and PSD size when contacted by TetTx + presynaptic terminals and more likely contained a spine apparatus (Zhu et al , 2021 ). The input‐specificity of SP recruitment upon activity perturbation is also supported by previous reports showing that high‐frequency stimulation in the dentate gyrus enhances SP immunoreactivity selectively in the corresponding stimulated layers (Yamazaki et al , 2008 ; de Solis et al , 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the lack of homeostatic modifications to overall synaptic AMPAR levels observed when purified TeNT was exogenously applied prior to and throughout synapse formation and maturation ( Harms and Craig, 2005 ). In contrast to the apparently smaller PSDs we observed, another study using mice expressing TeNT in excitatory principal neurons reported slightly increased PSD volumes at mushroom-type spines, measured by 3D electron microscopy (EM) ( Sando et al, 2017 ; Zhu et al, 2021 ). However, in agreement with our results, PSD volume was reduced at stubby, thin and filopodial spines ( Zhu et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 96%
“…The postsynaptic calcium homeostasis of glutamatergic PNs as well as local translation in spines are thought to be regulated by a part of the SER network called the spine apparatus (SA) 53,54 . Curiously, many excitatory synapses lack the mitochondria and SA 38,55 , but the underlying reasons and the functional implications of this heterogeneity are poorly understood. Prior EM studies, including recent work from our group, raise the possibility that subcellular localization of these organelles is influenced by sensory stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Prior EM studies, including recent work from our group, raise the possibility that subcellular localization of these organelles is influenced by sensory stimuli. However, this notion is based on indirect observations in electrically stimulated brain slices and excitatory neurons whose glutamate secretion was permanently blocked in vivo throughout development 38,55 . We found that, regardless of sensory experience and neuronal activity source, the mitochondria were more likely to be anchored in MSBs than in SSBs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation